A CASE SERIES OF DRUG-INDUCED THYROIDITIS - Yin, Joey Soon Jun; Sambamoorthy, Vijayrama Rao; Lee, Xe Hui (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Drug-induced thyroiditis is a relatively rare condition which is characterised by the inflammation of the thyroid gland after exposure to certain medications, with contrast agents and amiodarone being our main focus in this case series. CASE Case 1. A 40-year-old female with temporal bone squamous cell carcinoma and no prior thyroid disorder was undergoing radiotherapy and cisplatin-based chemotherapy and lost 5 kg within a month. Clinically, the patient was euthyroid. Initial thyroid function test (TFT) showed TSH <0.01 mIU/L (0.27–4.20) and fT4 35 pmol/L (12–22). Carbimazole 20 mg OD and propranolol 20 mg BD were started. Despite optimising carbimazole dose to 40 mg OD, repeated TFT after 10 days showed TSH <0.01 mIU/L, fT3 8.6 pmol/L (3.1–6.8), fT4 62 pmol/L. Anti-TSH receptor and anti-TPO antibodies were negative. Thyroid ultrasonography showed bilateral spongiform thyroid nodules (TR1). With a history of CT-simulation radiotherapy with 21,000 mg iodine-based contrast given 1 month prior, a diagnosis of contrast-induced thyroiditis was made. Prednisolone 40 mg OD (1 mg/kg) was initiated while carbimazole was tapered off over a month. Patient became biochemically euthyroid after three months of corticosteroids. Case 2. A 75-year-old man with no prior thyroid disorder and a recent history of coronary angiography presented with multiple episodes of ventricular tachycardia, requiring repeated synchronised cardioversion and multiple boluses of IV amiodarone 150 mg. Patient had palpitations but no signs of hyperthyroidism. TFT revealed TSH 0.1 mIU/L, fT3 5.5 pmol/L, fT4 33 pmol/L. Carbimazole 20 mg OD was started. Anti-TSH receptor and anti-TPO antibodies were negative. Diagnosis of type 2 amiodarone-induced thyroiditis was made; thus the patient was started on prednisolone 25 mg OD (0.5 mg/kg). Carbimazole was subsequently stopped, while prednisolone was gradually tapered off. Patient became biochemically euthyroid after one month of corticosteroids. CONCLUSION These cases are two types of drug-induced thyroiditis—contrast-induced thyroiditis and type 2 amiodarone-induced thyroiditis. Both cases showed hyperthyroidism biochemically but were clinically asymptomatic. It is crucial to make an accurate diagnosis to ensure appropriate treatment. Steroids played a major role in the treatment, while antithyroid drugs are less effective.